Culture and the politics of sustainable development in the GCC: identity between heritage and globalisation. Issue 5 (4th July 2019) - Al-Zo'by, Mazhar
ABSTRACT: Recognising the limits of the conventional global framework for sustainable development policies, the UN has recently accorded "culture" a central status in its universal vison for transformative development. However, many experts have voiced concern that the use of culture as a development strategy has not generated adequate community-based indictors for meaningful sustainability. Furthermore, the promotion and incorporation of culture into sustainable development strategies has largely and ambiguously remained within the confines of neo-liberal globalisation discourse. This article aims to examine the limits of culture-based sustainable development in the GCC region, as expressed in UN-inspired national development visions.